Strategi Pengembangan UKM Gethuk Pisang Guna Melestarikan Makanan Tradisional - Cahyono, Wahyu Eko; Kunhadi, Dedy (Universitas Suryakancana, 2020)
Abstract— Small and medium enterprises (SMEs) are business sectors that play an important role as a backbone of a nation or region